Children's Intergroup Attitudes: Insights From Iran. Issue 5 (24th March 2020) - Yazdi, Haleh; Barner, David; Heyman, Gail D.
Abstract : Children generally favor individuals in their own group over others, but it is unclear which dimensions of the out‐group affect this bias. This issue was investigated among 7‐ to 8‐year‐old and 11‐ to 12‐year‐old Iranian children ( N = 71). Participants evaluated in‐group members and three different out‐groups: Iranian children from another school, Arab children, and children from the United States. Children's evaluations closely aligned with the perceived social status of the groups, with Americans viewed as positively as in‐group members and Arabs viewed negatively. These patterns were evident on measures of affiliation, trust, and loyalty. These findings, which provide some of the first insights into the social cognition of Iranian children, point to the role of social status in the formation of intergroup attitudes.